Climate Change Exposition Reading Materials for Senior High School Textbook: Students’ Needs Analysis - Geyereni Maretika Noto; Sofendi Sofendi; Hartono Hartono; Ratu Ilma Indra Putri; Rita Inderawati (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research intends to dig out the Senior High School students' needs in English reading materials development based on climate change material revised by students', and teachers' views. The data were obtained by applying a questionnaire and semi-structured interviews. The data are described both quantitatively and qualitatively. The outcomes of the need analysis represent that: 1) English is important to students' future careers, (2) students’ English proficiency is at the beginner level, 3) students still get some hardship in writing skills, 4) the type of text needed is an exposition text, 5) it has connected between English reading materials and the content subject materials, 6) students still run short of awareness about climate change material, 7) There is still the limitation of climate change as the English reading materials, 8) two major causes for connecting climate change material into educational materials are to increase the awareness of students. As a consequence of the needs, it is important to develop supplementary exposition reading materials by connecting climate change which fit the students’ English proficiency and can help out their study program.